DEFINING 'PERSONAL CONSUMPTION' IN DRUG LEGISLATION AND SPANISH CANNABIS CLUBS. Issue 1 (28th January 2019) - Marks, Amber
Abstract: This article provides an analysis of the normative framework for Spanish cannabis clubs by contextualizing it within the growing body of comparative constitutional law that recognizes legal obstructions to personal drug consumption as intrusions of the right to privacy. Article 3(2) of the United Nations Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, 1988 relieves State parties from the Article's obligation to criminalize drug possession and cultivation for 'personal consumption' when doing so would conflict with their constitution or basic concepts of their legal system. Spain relied on Article 3(2) in its decision not to criminalize conduct involving personal consumption. The Spanish judiciary has had to consider the legal implications of collective consumption and cultivation in the form of cannabis clubs. In addition to operating in a grey area of domestic law, Spain's cannabis clubs straddle the blurred boundary in international and European legal instruments between 'personal consumption' and 'drug trafficking'. This article explores the theoretical and doctrinal implications of both Spanish law on cannabis clubs and comparative human rights law on drug use to outline the potential contours of a constitutionally protected zone of privacy pertaining to cannabis use in a social context.